2015
DOI: 10.17795/zjrms983
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Frequency of HLA-B27 in Patients Engaged With Seronegative Spondyloarthropathies in Kashan, Iran

Abstract: Background: Seronegative Spondyloarthropathies (SNSAs) are referred to a group of diseases with same clinical and genetic features. Objectives: Due to lack of data about HLA-B27 prevalence in patient with SNSA in Kashan this study was conducted to determine the status of HLA-B27 in these patients. Patients and Methods:This cross sectional study was conducted on 294 patients suffered from SNSA. Presence or absence of HLA-B27 was checked by serological method using Greener kit. Results were analyzed with SPSS-16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…21 HLA-B27 was found to be more commonly associated with AS (62.8%) followed by ReA (21.2%) and PsA (12.2%) in our study. Kamal et al, 2 observed that HLA-B27 was predominantly associated with AS (69%) similar to our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…21 HLA-B27 was found to be more commonly associated with AS (62.8%) followed by ReA (21.2%) and PsA (12.2%) in our study. Kamal et al, 2 observed that HLA-B27 was predominantly associated with AS (69%) similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…Spondyloarthritis (SpA) is a group of inflammatory arthritis, with common clinical manifestations, etiological factors and genetic characteristics, with a strong link to class I HLA antigens. [1][2][3] This group of diseases is characterized by its axial involvements and absence of rheumatoid factor, 4 frequently affecting sacroiliac (SI) joints of the spine that connects spine with the pelvis. SpA also has predispose to major inflammation in joints throughout the body.…”
Section: Introductionmentioning
confidence: 99%
“…HLA-B27 has a long history of being strongly genetically linked to AS. 34,35 In our investigation, HLA-B27 was shown as frequently linked to AS (62.8%) than to ReA (21.2%) or PsA (12.2%), similar results stated by Kamal et al 2 that HLA B27 mainly was related to AS (69%). After rheumatoid arthritis, the second most prevalent inflammatory arthritis in India is spondyloarthritis.…”
Section: Discussionsupporting
confidence: 84%
“…Spondyloarthritis (SpA) is a subset of inflammatory arthritis with a significant genetic correlation to class I HLA antigens with clinical manifestations and etiological variations. [1][2][3] This group of illnesses usually affects the sacroiliac (SI) joints, and they are distinguished by their axial involvement and lack of rheumatoid factor. 4 SpA also prefers to affect the body's key joints, and along the length of the spine, it produces pain, stiffness, and twinging (suffer a sudden, sharp localized pain).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, B*2746, B*2749, B*2767, B*2702 and B*2705 subtypes were detected among Ankylosing Spondylitis patients in Turkey [32]. HLA-B27 was shown to have highest prevalence in ankylosing spondylitis and least prevalence in juvenile rheumatoid arthritis among Iranian population [33]. Studies reported an increased prevalence of HLA-B27 in rheumatoid arthritis patients in Turkey [34].…”
Section: Discussionmentioning
confidence: 95%